Atrial fibrillation is associated with different levels of physical activity levels at different ages in men - Drca, N.; Wolk, A.; Jensen-Urstad, M.; Larsson, S. C. (Heart, 2014)
Objective This study examines the influence of physical activity at different ages and of different types, on the risk of developing atrial fibrillation (AF) in a large cohort of Swedish men.